IMPLEMENTATION OF LAWS REGARDING ECONOMIC CRIME IN THE ECONOMIC FIELD IN LAW NUMBER 20 OF 2001 CONCERNING ERADICATION OF CRIMINAL ACTIONS OF CORRUPTION - Muhamad Irfan Florid; Nandang Sambas (LPPM Universitas Trunojoyo Madura, 2023)
Crimes against the economy pose a significant challenge to the development and maintenance of economies across the world. The Indonesian government has enacted a number of laws, notably Law Number 20 of 2001 concerning the Eradication of Corruption Crimes, in order to address this issue and find a solution. This legislation plays a significant part in the fight against economic criminal activity in all areas of the economy. The purpose of this research is to investigate the challenges and elements that contribute to the success or failure of anti-corruption efforts. This study employed an empirical research method, which is a type of legal research that involves examining primary and secondary data, specifically data obtained directly from the public through field studies and literature studies. Field studies and literature studies are two of the most significant challenges facing efforts to eradicate economic crime in Indonesia. This study has significant implications that will enhance knowledge, provide advice, and provide suggestions to boost the efficacy of the execution of Law Number 20 of 2001 in eliminating economic crimes. These implications are crucial because this research will promote understanding, provide direction, and provide recommendations. It is anticipated that these repercussions will serve as the foundation for specific policies and actions that will boost the level of success achieved in the fight against economic crimes in Indonesia.